Sistematic Literature Review: Exploring of Determinant Factors For The Implementation of The Effectiveness of The Construction of The Trans Sumatra Toll Road, Indonesia - Haris Haris; Rully Indrawan (Dinasti Publisher, 2024)
There are many researchers who are interested in conducting research by raising the issue of factors that influence the implementation of the effectiveness of toll road construction and its impact on the potential economic growth of the region through which it passes, but have difficulty finding what are the most dominant factors that can be used to explain variations in their influence on development. toll road. This research aims to reveal, explore and analyze determinant factors that can explain variations in their influence on the effectiveness of the construction of the Trans Sumatra toll road, Indonesia. This research used 1,100 journals and the existing journal data. The analysis technique uses systematic literature review analysis with three stages of analysis including identification, screening and included. The novelty produced in this research is that the researcher identified several determinant factors that can explain variations in their influence on the effectiveness of toll road construction which can be used by researchers who are interested in raising the issue of toll road construction. The results of this research show that there are several determinant factors that can explain variations in their influence on the effectiveness of toll road construction, both directly and indirectly, including the variables of logistics cost efficiency, regional development, land use changes, toll procurement costs, local revenue, inter-city transportation, growth. regional economy, performance of the transportation and warehousing sectors, performance of the tourism sector, and performance of the agriculture, forestry and fisheries sectors.